Factors influencing readiness of cashless system in Malaysia - Kaladevi, Shunmugam (2021)
The government of Malaysia has intended to transform Malaysia into a digital era by 2020, as stated in the Financial Blueprint 2011. Growth in electronic payments and mobile banking are significantly increasing, but private researchers have mentioned that Malaysia is not ready to meet this goal by 2020 due to a lack of security and data privacy. The objective of this paper is to determine the factors influencing readiness level of Malaysia in adopting digital payments and going cashless. Key variables like usage, awareness, trend analysis and descriptive comparison between cash and cashless economy are being used as core parameters in this study. Regression analysis was conducted to generate the outcomes. The results indicated that Malaysia was 20% cashless in 2018. Hence, the country is still far from meeting its aim of wanting to be operating in full cashless mode by 2020. It has been deduced that Malaysia may potentially need an estimated amount of 10 years or more to be able to operate fully in cashless mode and completely utilise digital payments as routine paying methods. Furthermore, sufficient strategic moves and action plans to boost digital payments and awareness in assisting transformation towards digitalisation are required in Malaysia. Also, involvement from all parties, including profitable and non-profitable organisations from every economic sector will assist towards realising this digital transformation.